Ineffectiveness of an administrative act (can. 38 CIC) - DZIERŻON, GINTER (Prawo Kanoniczne, 2017)
The author of the presented article carried out a thorough interpretation of canon 38 CIC. According to the analyses he carried out, canon 38 CIC specifies the rules concerning the ineffectiveness of a particular administrative act only from one view, namely from the perspective of the contents of an act. The solutions suggested in the regulation remain in close relation with the rule of legality. The author believes that the ecclesial legislator is far form positivistic legalism since he makes it possible to insert a derogative clause concerning a specific case. According to the author, such a solution is necessary because a given law cannot be the sole point of reference in exercising power. This is because in exercising administrative power one often comes across very specific situations. Therefore, including such a clause should be considered as “normae singulares”.